Dr. Mulk Raj Anand’s Novel Untouchable: A Reflected Ray of Gandhian Ideals - Malajyoti Gogoi, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Untouchability is a deep rooted social evil. From time immemorial, the existence of this evil cannot be denied though equality is the slogan of the 21st century, but still the prevalence of this social evil badly contaminate the society. Mahatma Gandhi , the Father of Nation said untouchability as social disgrace on Hindusim. He devoted his life to establish equality and peace through his revolutionary effort. He occupies the top most position in the history of India as humanist, reformist, socialist who have innumerable saintly and spiritual qualities. Indian English literature was grosslly occupied with Gandhian conscience socially, politically and culturally. M.K. Naik writes in his History of Indian English Literature thus: